The effect of low energy protons on the operational characteristics of EPIC-MOS CCDs - Abbey, A.F.; Ambrosi, R.M.; Smith, D.R.; Kendziorra, E.; Hutchinson, I.; Short, A.; Bennie, P.; Holland, A.; Clauss, T.; Kuster, M.; Rochow, W.; Brandt, M.; et al. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
The University of Tubingen 3.5 MeV Van de Graaf accelerator facility was used to investigate the effect of low energy protons on the performance of the European Photon Imaging Camera (EPIC), metal-oxide semiconductor (MOS), charge coupled devices (CCDs). Two CCDs were irradiated in different parts of their detecting areas using different proton spectra and dose rates. Iron-55 was the calibration source in all cases and was used to measure any increases in charge transfer inefficiency (CTI) and resolution of the CCDs as a result of proton damage. Additional changes in the CCD bright pixel table and changes in the low X-ray energy response of the device were examined. The Monte Carlo code SRIM was used to model the effect of a 10 MeV equivalent fluence of protons interacting with the CCD. Since the non-ionising energy loss (NIEL) function could not be applied effectively at such low proton energies. From the 10 MeV values, the expected CTI degradation could be calculated and then compared to the measured CTI changes.